Strategi Think Pair Share dan Jigsaw: Manakah yang Lebih Efektif untuk Kemampuan Pemecahan Masalah Siswa? - Arief Cahyo Utomo; Zaenal Abidin; Henry Aditia Rigianti (Profesi Pendidikan Dasar, 2020)
This study aimed to find out the different of efectiveness of Think Pair Share (TPS) and Jigsaw learning model on problem solving ability of 6th grade students. This study compared which has a greater effect on problem solving ability of 6th grade students. This study was a quasy experiment. The subjects of this study were 6th grade elementary school students in Ngadirojo Kidul, Wonogiri, Indonesia. Data collection used were pretest and post test technique. Data analysis used was Anova with T-test where previously preceded by prerequisite test (homogenity test and normality test). The result of this study is there is difference between TPS learning model and Jigsaw learning model. TPS learning model has a greater influence in improving problem solving ability of 6th grade elementary school students.